Comparison of Humphrey MATRIX and Swedish interactive threshold algorithm standard strategy in detecting early glaucomatous visual field loss - Prema, Raju; George, Ronnie; Hemamalini, Arvind; Sathyamangalam Ve, Ramesh; Baskaran, Mani; Vijaya, Lingam (Indian journal of ophthalmology, 2009)
The aim of this study was to compare the Humphrey MATRIX visual field (frequency doubling technology threshold) and Swedish interactive threshold algorithm (SITA) standard strategy white on white perimetry in detecting glaucomatous visual field loss. Twenty-eight adult subjects, diagnosed to have glaucoma at a tertiary eye care hospital, who fulfilled the inclusion criteria, were included in this prospective study. All subjects underwent a complete ophthalmic examination. Subjects with glaucomatous optic disc changes underwent repeat perimetric examination on the same day with the Humphrey visual field analyzer (HFA II) and Humphrey MATRIX, the order of testing being random. Only reliable fields, where the HFA results corresponded to the disc changes were considered for analysis. A cumulative defect depth in each hemifield in both HFA and MATRIX reports was calculated. Thirty-seven eyes of 24 subjects had reliable fields corresponding to optic disc changes. The mean age of the subjects was 56 +/- 12 years. There were 12 males and 12 females. The test duration was significantly less on the MATRIX, mean difference in test duration was -81 +/- 81.3 sec ( p p = 0.55, p = 0.64 respectively) and a positive correlation coefficient of 0.63 and 0.72 respectively. Poor agreement was found with the glaucoma hemifield test. The Humphrey MATRIX takes less time in performing the test than SITA Standard and shows good correlation for mean deviation and pattern standard deviation. However, the glaucoma hemifield test showed poor agreement. The Humphrey MATRIX diagnoses were similar to established perimetric standards.